Novel Innovation of Subsidized Fertilizers based on Soil Variability and Farmer’s Perception - Elisa Wildayana; M. Edi Armanto; Imron Zahri; M. Yamin Hasan (Muhammadiyah University Press, 2017)
The study aimed to find novel innovation and research of subsidized fertilizers based on soil nutrient variability and farmer’s perception in rice farming. This study uses a completely randomized design with four natural treatments, a one-way Anova and Tukey HSD Test as well as multiple linear and cubic regressions. The fertilizer uniformity on varied ricefields was a big failure because it causes fertilization becoming ineffective, inefficient and unsustainable. Ricefield variability (due to geomorphogenesis, pedogenesis, interflow flow, vegetation distribution, land use patterns, and fertilizer application) causes not optimized fertilization (dose, balance, time, methods of fertilization). The perception of farmers can create conflicts of interest, which are determined as normal, unavoidable and natural. Short-term research target is how fertilization in the field is done effectively, efficiently, and sustainably, whereas long-term target is to generate new sources of wealth, fertilization technology based on soil science knowledge, forming professional researcher, the great inventions of patents, cooperation media between scientists, technocrats and bureaucrats and research funding.